Perbedaan Sikap Pemilih Pemula Antara Peserta Dan Bukan Peserta “Roadshow Pendidikan Pemilu” - Almira Ditrya Kartikatantri, (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2015)
AbstractThis study aims to determine the differences in attitudes between students of D3 Communication Studies, University of Indonesia as a participant and student D3 and Political Studies Social Sciences University of Indonesia, which is not a participant ‘Roadshow Pendidikan Pemilu’ in the General Election of 2014 raised as one requirement for undergraduate exams S1 Department of Public Relations Faculty of Communication Sciences, University of Padjadjaran. This study used quantitative methods, based on Persuasion Theory (Instrumental Theory of Persuasions) proposed by Holland, Janis, and Kelly. The test used is the Mann-Whitney test with a descriptive analysis techniques and interferential. The results showed that there were significant differences in attitudes between the samples. Based on these results, the authors suggested that the team AyoVote fix the contents of the message to make it more structured and more interesting to be delivered to the participants, so the effect will be more significant given. Also to increase the frequency of implementation of activities, so that more people who know a variety of basic science and politics will be aware of their obligations as Indonesian people who have the right to vote to determine the future of his country. This means that the activities carried out successfully change the attitudes of participants became more positive and match the AyoVote Team expectation. Based on these results, the authors suggested that the team AyoVote fix the contents of the message to make it more structured and more interesting to be delivered to the participants, so the effect will be more significant, also to increase the frequency of implementation of activities, so the more people who know the basic politic and conscious political duty as Indonesian people who have the right to vote to determine the future of his country. Abstrak Penelitian ini bertujuan untuk mengetahui perbedaan sikap antara mahasiswa D3 Studi Komunikasi Universitas Indonesia sebagai peserta dan mahasiswa D3 Studi Ilmu Sosial dan Politik Universitas Indonesia yang bukan sebagai peserta “Roadshow Pendidikan Pemilu” dalam Pemilihan Umum Legislatif 2014. Dalam penelitian ini digunakan metode kuantitatif, berdasarkan Teori Persuasi (Instrumental Theory of Persuassions) yang dikemukakan oleh Hovland, Janis, dan Kelly. Pengujian yang digunakan adalah uji beda Mann-Whitney dengan teknik analisis deskriptif dan interferensial. Hasil penelitian menunjukkan bahwa terdapat perbedaan sikap yang signifikan antara sampel yang mengikuti dengan yang tidak mengikuti kampanye “Roadshow Pendidikan Pemilu” yang diadakan oleh tim AyoVote. Artinya kegiatan yang dilakukan berhasil mengubah sikap peserta kegiatan menjadi lebih positif sesuai dengan harapan pelaksana kegiatan. Berdasarkan hasil penelitian ini, penulis menyarankan agar tim AyoVote membenahi isi pesan supaya lebih terstruktur dan lebih menarik untuk disampaikan kepada peserta, sehingga pengaruh yang diberikan akan dapat lebih signifikan dan menambah frekuensi pelaksanaan kegiatan, sehingga makin banyak orang yang tahu berbagai ilmu dasar politik dan sadar akan kewajibannya sebagai masyarakat Indonesia yang memilki hak pilih untuk menentukan masa depan negerinya.